2021
DOI: 10.1016/j.eclinm.2021.100726
|View full text |Cite
|
Sign up to set email alerts
|

Major differences in clinical presentation, diagnosis and management of men and women with autosomal inherited bleeding disorders

Abstract: Background In recent years, more awareness is raised about sex-specific dilemmas in inherited bleeding disorders. However, no large studies have been performed to assess differences in diagnosis, bleeding phenotype and management of men and women with bleeding disorders. Therefore, we investigated sex differences in a large cohort of well-defined patients with autosomal inherited bleeding disorders (von Willebrand disease (VWD), rare bleeding disorders (RBDs) and congenital platelet defects (CPDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…Significant diagnostic delays, which occur in most BDs, hamper accurate management especially for WGBD 3,6,23 . HMB can be the sentinel symptom of a BD, particularly in adolescents 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant diagnostic delays, which occur in most BDs, hamper accurate management especially for WGBD 3,6,23 . HMB can be the sentinel symptom of a BD, particularly in adolescents 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Approximately one in five women who presents to a gynaecologist with heavy menstrual bleeding (HMB) have an underlying BD 1,2 . Yet, BD under‐diagnosis remains very common with median diagnostic delays of 8–16 years in women and girls 3–6 . Identification of haemophilia carriers (HCs) is inadequate, with genetic testing often delayed (median age 30 years), and 31% of women being unaware of their carrier status at time of delivery, despite a known family history 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Although this could partially be explained by a first bleeding episode at different ages, it has also been shown that the diagnostic delay following the first bleeding episode is longer in women than men. 8 Delayed diagnosis may result in missed treatment opportunities and increased morbidity (both medical and psychological). It is thus important to increase knowledge and awareness of VWD among (general) clinicians and public.…”
Section: Challenges In the Diagnosis Of Vwdmentioning
confidence: 99%
“…People with bleeding disorders (PBD) commonly experience delays in diagnosis despite presenting with ‘(ab)normal’ bleeding symptomatology 1‐4 . These delays lead to poorer health outcomes, impair quality of life and may increase the risk of life‐threatening or fatal bleeding 1‐3,5 .…”
Section: Introductionmentioning
confidence: 99%